2012
DOI: 10.5603/fhc.2012.0014
|View full text |Cite
|
Sign up to set email alerts
|

Atrial expression of the CCN1 and CCN2 proteins in chronic heart failure

Abstract: Previous studies have reported the upregulation of CCN proteins early after acute heart injury. The aim of the present work was to evaluate the expression of the CCN1 and CCN2 proteins and their regulation by angiotensin II in the atrial myocardium of a chronically failing heart. Male adult mice were subjected to ligation of the left coronary artery to produce myocardial infarction (the MI group), and 16 of them were treated for 12 weeks with the AT1 receptor antagonist telmisartan (the MI-Tel group). Sham-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…It has also been reported that CCN1 expression can be induced by angiotensin II and phenylephrine or ischemic stress in cardiomyocytes. Expression of CCN1 is nearly absent in the non-failing heart, whereas increased CCN1 levels have been detected in the atrial myocardium in an animal model of chronic heart failure [21]. Interestingly, Yoshida et al found that CCN1 increased the survival of myocytes by activating the integrin β1-Akt pathway under conditions of oxidative stress, whereas knockdown of CCN1 decreased the number of surviving cells under these conditions, indicating that CCN1 is a protector of ischemic myocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that CCN1 expression can be induced by angiotensin II and phenylephrine or ischemic stress in cardiomyocytes. Expression of CCN1 is nearly absent in the non-failing heart, whereas increased CCN1 levels have been detected in the atrial myocardium in an animal model of chronic heart failure [21]. Interestingly, Yoshida et al found that CCN1 increased the survival of myocytes by activating the integrin β1-Akt pathway under conditions of oxidative stress, whereas knockdown of CCN1 decreased the number of surviving cells under these conditions, indicating that CCN1 is a protector of ischemic myocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Ccn1 (gene name in Fig. 3 is Cyr61) is a matricellular protein whose expression has been associated with heart failure 47 . Mice deficient for Col15a1 (type XV collagen) also have heart defects 48, 49 .…”
Section: Resultsmentioning
confidence: 99%
“…The stimulatory effects of S1P on an increase in the expression of CCN1 and CCN2 are substantially faster than those on the expression of COX2, indicating that CCN proteins are the upstream effectors of COX2 upregulation. Previous studies have shown that CCN1 and CCN2 are simultaneously upregulated in response to various stimulants, which, in turn, modulate multiple functions in certain mammalian cells [44,45,46]. Considering the critical roles of CCN1 and CCN2 in the regulation of follicular development and ovulation, we sought to investigate the involvement of CCN proteins in the S1P-induced upregulation of COX2.…”
Section: Discussionmentioning
confidence: 99%